Letter to the editor regarding Effectiveness of bracing combined with exercise-based treatment of adolescent idiopathic scoliosis: Assessing the synergistic benefits: A systematic review - Colak, Tugba Kuru; Akcay, Burcin; Apti, Adnan; Dereli, Elif Elcin (Wolters Kluwer Health, 2025)
[Abstract Not Available]
Keywords: Quality-Of-Life; Deformity; Health